Mutable objects, places and chronologies. (February 2021) - Sainsbury, Victoria A.; Bray, Peter; Gosden, Chris; Pollard, A. Mark
Abstract: Abstract : Mutability—the ability to change form and substance—is a key feature of glass and metals. This quality, however, has proven frustrating for archaeological and archaeometric research. This article assesses the typological, chemical and theoretical elements of material reuse and recycling, reframing these practices as an opportunity to understand past behaviour, rather than as an obstacle to understanding. Using diverse archaeological data, the authors present case studies to illustrate the potential for documenting mutability in the past, and to demonstrate what this can reveal about the movement, social context and meaning of archaeological material culture. They hope that through such examples archaeologists will consider and integrate mutability as a formative part of chaînes opératoires.